The Dorsal Anterior Cingulate Cortex Modulates Dialectical Self-Thinking - Wang, Fei; Peng, Kaiping; Bai, Yang; Li, Rui; Zhu, Ying; Sun, Pei; Guo, Hua; Yuan, Chun; Rotshtein, Pia; Sui, Jie (Frontiers in Psychology, 2016)
Dialectical self-thinking involves holding the view that one can possess contradictory traits such as extraverted and introverted. Prior work has demonstrated that the dorsal part of anterior cingulate cortex (dACC) plays a crucial role in conflict monitoring as well as self-related processing. Here we tested the function of dACC in dialectical self-thinking using a modified classical self-referential paradigm (self- vs. other-referential thinking), in which participants had to make a judgment whether a simultaneously presented pair of contradictory or non-contradictory traits properly described them while brain activity was recording using functional magnetic resonance imaging (fMRI). The data showed that activity in the dACC during the processing of self-relevant conflicting information was positively correlated with participants' dispositional level of naïve dialecticism (measured with the Dialectical Self Scale). Psychophysiological interaction (PPI) analyses further revealed increased functional connectivity between the dACC and the caudate, middle temporal gyrus and hippocampus during the processing of self-relevant conflicting information for dialectical thinkers. These results support the hypothesis that the dACC has a key role in dialectical self-thinking.